Language and literacy in social practice - Maybin, Janet; Maybin, Janet; Open University (Clevedon, Avon, England : Philadelphia : Multingual Matters Ltd. in association with the Open University, 1994)
This volume contains a collection of seminal articles and recent research which are important reading for anyone wanting to understand current theoretical developments within the field of language and literacy studies.
Includes bibliographical references and index.
Keywords: Literacy -- Social aspects; Sociolinguistics; Language and languages -- Study and teaching -- Social aspects; Educational anthropology